Relación entre inversión pública en telecomunicaciones y el acceso y uso de los servicios de telecomunicaciones, Loreto 2012-2021 - Gomez Cordova, Gino Moises (2023)
Access to telecommunications services is essential for people's development, so investment could be a great driver for access to telecommunications services. In this sense, the present thesis proposes as its main objective to determine the relationship that exists between Public Investment in Telecommunications and the access and use of Telecommunications services in Loreto, period 2012-2021 and the research is of a quantitative and correlational type since the research variables are quantified and related, developed with a non-experimental design and had as a study population all Loreto households in the period 2012-2021. The investigation determined R2=0.3029 and Prob > F = 0.0993 being greater than 5%, so it is not significant, concluding that public investment in telecommunications does not determine the access and use of telecommunications services in the Loreto region, period 2012-2021. On the other hand, a growing trend was identified in the access to telephone, internet and cable television services, being beneficial for the population of Loreto.